2015
DOI: 10.1080/02791072.2015.1079669
|View full text |Cite
|
Sign up to set email alerts
|

Motivation for Treatment and Motivation for Change in Substance-Dependent Patients with Co-Occurring Psychiatric Disorders

Abstract: The aims of this study were to examine the relationship between motivation for treatment and for change, and to explore their role in the prediction of treatment completion. The sample was composed of 560 predominantly polydrug-using inpatients with co-occurring psychiatric disorders. Motivation for treatment was assessed with the Motivation for Treatment Scales, and motivation for change was measured with the Readiness to Change Questionnaire. Patients indicated strong motivation to change illegal drug and al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 31 publications
2
3
0
Order By: Relevance
“…Our finding concerning the reduced relapse risk associated with higher baseline motivation was expected, and it is in accordance with a previous study reporting a positive association between high initial readiness for substance use change and treatment outcome (i.e. retention) among inpatients with COD [26]. Our results suggest that baseline motivation may be a particularly relevant risk factor of relapse among these patients.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our finding concerning the reduced relapse risk associated with higher baseline motivation was expected, and it is in accordance with a previous study reporting a positive association between high initial readiness for substance use change and treatment outcome (i.e. retention) among inpatients with COD [26]. Our results suggest that baseline motivation may be a particularly relevant risk factor of relapse among these patients.…”
Section: Discussionsupporting
confidence: 92%
“…These variables included younger age [15,18,19], lower education, and unstable living arrangements [20], whereas previous research on putative gender differences in SUD treatment outcomes revealed mixed results [21][22][23]. Among psychological variables, both baseline motivation [24][25][26] and baseline mental distress level (i.e. symptoms of anxiety/depression) [24,[27][28][29] have been found to be associated with SUD treatment outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…The first objective of the study was to determine the properties of the MTQ-8. The RA confirmed the adequate construct validity and the structure of the questionnaire in two dimensions represented by the subscales proposed by van , also identified by de Weert-van et al (2015): Motivation to initiate Treatment and Readiness for Change. The analyses carried out showed that both subscales are adequate measurement instruments, although it was necessary to merge Items 5 and 7 in the latter subscale.…”
Section: Discussionsupporting
confidence: 75%
“…Related to this accumulating evidence is recent Dutch research of substance-dependent patients with co-occurring psychiatric disorders (De Weert-Van Oene et al 2015). In this research, "motivation for treatment" was analytically distinguished from "motivation for change."…”
mentioning
confidence: 97%